Análise multitemporal da dinâmica do usos e ocupação do baixo curso do rio de Apodi - Mossoró (1989-2009) - Rocha, Alexsandra Bezerra da (2011)
Through a geoenvironmental analysis, this work is related to the study of a hidrographic basin as a geographical analysis category. The hydrographic basin of the Apodi-Mossoró river represents 27% of the territory of the state of Rio Grande do Norte, covering a total area of 14.271 km2, having a spatial cutting for this study, the lower course of the mentioned river, which covers 973 km2. Regarding the geodiversity, it is characterized as an area with a presence of a plateau, coastal tablelands, fluviomarine plain, of coastal band with beaches, cliffs and dunes. In this context, the work had the objective to do an analysis of the environmental framework considering the dynamics of the use and occupation, through a study of a multitemporal scale from 1989 to 2009, basically identifying and putting on a spatial scale the geoenvironmental units, the pressure of use, using remote sensoring, the geographical information system for the handling and information crossing, qualitative quantitative research, obtaining as a final result a set of seven maps. The result also indicated, in hectares, a percentage of economic activities in 1989 as: 16,4% of cyclical cultures, 19,2% of perennial culture, 0,04% of petroliferous areas, 64,4 % of salt-mines (craft and industrial). In 2009, the perennial cultures represented 32,7% , the petroliferous activities 33,4%, saltmines 34% (craft and industrial) and the breeding of crabs and other crustaceous 2%. Therefore, it was observed a growth of 126% for perennial cultures, 1.847% for petroliferous activities and 28,50% for alt-mine activities. We can understand that the different forms of use alters the environmental dynamics of the studied area, contributing to the intensification of fluvial processes, to the deposition of sediments, to the silting up process, to the erosion, to the destruction of cilliary woods and to the ecosystem´s mangal. The changes in the low course of Apodi-Mossoró river, correspond to the very significant modifications of the original morphology and in the dynamics of geomorphological processes, in the rate of average annual fluvial discharge and in the rate of transportation of the sediments. Those facts, associated with the environments of inadequate occupation foster the emergence of areas with high exposure of environmental quality.